2002
DOI: 10.1002/ijc.10621
|View full text |Cite
|
Sign up to set email alerts
|

Absence of simian virus 40 in human brain tumors from northern India

Abstract: Simian virus 40 (SV40), a monkey polyomavirus, was a contaminant of early poliovirus vaccines administered to millions of individuals in the 1950s and early 1960s. SV40 causes brain tumors in laboratory animals, and SV40 DNA sequences have been variably identified in human choroid plexus tumors and ependymomas. We studied the possible association between SV40 and human brain tumors in northern India, where humans have frequent contact with SV40-infected rhesus macaques. DNA from pathologic specimens from 33 ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 21 publications
1
46
2
Order By: Relevance
“…We disagree with the interpretation of the results presented in the article by Engels et al, 1 and we believe that statements in the text are unsubstantiated and misleading.…”
Section: Dear Sircontrasting
confidence: 70%
“…We disagree with the interpretation of the results presented in the article by Engels et al, 1 and we believe that statements in the text are unsubstantiated and misleading.…”
Section: Dear Sircontrasting
confidence: 70%
“…52 In vitro, repression of SV40 T-antigen function results in cellular senescence and loss of the transformed phenotype, 53 suggesting that a clonal-association with one or more copies of the SV40 Tantigen per tumor cell would be causally necessary. Previous studies that used quantitative PCR for detection of SV40 sequences in human tumors reported SV40 copy numbers substantially less than one viral copy per cell (1-100 copies per 0.5 lg of tumor DNA) 54 ; 0.12 in 14,000 cells, 55,56 or have been negative. 57,58 Although it has been argued that low SV40 copy numbers in human tumors are still compatible with an etiologic role, such low copy numbers, in combination with the uniform absence of sequences found in native SV40, argue against a hit and run mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, Engels et al (2002) used quantitative PCR (Q-PCR) to test for SV40 and to determine the amount of SV40 actually present in tumors. However, the sensitivity of their assay was so low that they estimated at 'less than 10' the total number of SV40 genomes present in six mouse tumors formed by the CRL-2162 SV40-positive mouse cell line (ATCC).…”
Section: Negative Reportsmentioning
confidence: 99%
“…Unfortunately, the GAPDH estimates were incorrect, leading to an error in their calculations of SV40 copy number in the cells. Engels et al (2002), stated that GAPDH is a single-copy gene. In fact, human cells contain 25 copies of highly homologous GAPDH sequences, 12 of which share extensive nucleotide identity with the universally known cDNA sequence (Hanauer and Mandel, 1984).…”
Section: Negative Reportsmentioning
confidence: 99%